Intellectual property rights and competition policy: patent rights, access to life-saving drugs in developing and least-developed countries under the TRIPS Agreement and the future of TRIPS after the Article 31 bis Amendment - Brucker, Johanna (Centre for Law and Society, 2026)
This paper examines the interface between intellectual property rights, the issuing of patent protection under the TRIPS Agreement and access to essential medicines. at affordable prices in developing and least-developed countries. It considers the link between patent protection under TRIPS and competition policies by highlighting the clash between intellectual property rights and competition law. The negative impact of intellectual property rights and patent protection on access to available and affordable drugs plays a major role in the discussion related to the international pharmaceutical market. In 1995 the World Trade Organization introduced the Agreement on Trade related Aspects of Intellectual Property Rights. Since the Doha Declaration was adopted in 2001, only a few countries have made use of the flexibilities under TRIPS. This study examines the use of TRIPS flexibilities for the access on essential drugs in developing and least-developed countries and sets out the impact of the Doha Declaration of 2001 and the Amendment to TRIPS of 2005 on the TRIPS Agreement. Governments worldwide are considering whether to ratify the Article 31 bis Amendment. This study argues that a failure to accept and use Article 31 bis will undermine the Doha Decision and the General Council Decision of 2003; it will result in an immense negative impact on health treatment for people in poor small countries. Furthermore, the paper discusses the interface between competition law and the intellectual property system under the TRIPS Agreement after the European Microsoft case and explores the relationship between patent protection under TRIPS, monopolies and anti-competitive behaviour in the market by abusing the dominant position granted by the exclusive patent right. Finally, it highlights factors influencing the future of TRIPS, suggests some action for an effective use of the flexibilities of TRIPS for a broader access on affordable and available medicines in developing and least-developed countries and seeks to examine the reconciliation of the clash between intellectual property rights and competition policies.